Blow-Up Solutions for a Singular Nonlinear Hadamard Fractional Boundary Value Problem. (23rd October 2020) - Bachar, Imed; Mesloub, Said
Abstract : We consider singular nonlinear Hadamard fractional boundary value problems. Using properties of Green's function and a fixed point theorem, we show that the problem has positive solutions which blow up. Finally, some examples are provided to explain the applications of the results.